Determining the Fisheries Consumption Preferences of Ege University Students - Hülya Saygı (Turkish Journal of Agriculture: Food Science and Technology)
Demand for fishery products rich in protein, vitamin, mineral and omega fatty acids is increasing day by day in order to meet the increasing nutritional needs of the world population. Despite being very beneficial fisheries, the amount of consumption in Turkey is very low compared to other countries. For this purpose, as an exemplary study, it has been tried to reveal the fishery consumption habits of students studying at Ege University. Faculties in Ege University have been considered as layers. In the study, a 25-question questionnaire was conducted face-to-face to 381 students selected according to the random sampling method between February and March 2019, and the results were obtained. The survey results obtained from the participants were evaluated using IBM SPSS 25.0 package program. The obtained results were evaluated by Chi-square analysis and Principal Component Analysis. Two group consumers emerged, representing coastal region 54.8% and Terrestrial region 45.2%. It has been determined that the most important reason for fish consumption in preference factors and availability is price. Ege University of students’ Consumer profiles; It was found to be different in terms of socio-demographic factors, consumption patterns, attitudes towards health and healthy food. As a result, it was determined that the fishery products were not consumed at the desired level in Ege University students. Accordingly, Ege University students should be made aware of increasing their consumption of fisheries. For this purpose, it is recommended to carry out promotions, advertisements and promotions that prove healthy.